2010
DOI: 10.3109/03009740903270607
|View full text |Cite
|
Sign up to set email alerts
|

The association of luteinizing hormone and follicle-stimulating hormone with cytokines and markers of disease activity in rheumatoid arthritis: a case–control study

Abstract: The significant associations between percentage changes in LH and FSH and percentage changes in key cytokines and several cross-sectional markers of disease activity may indicate that LH and FSH influence crucial points of the cytokine cascade in RA. This may help to explain, partially, why disease activity initiates or worsens during periods of increased LH and FSH, such as the postpartum period and the menopause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 28 publications
2
22
0
Order By: Relevance
“…After log-transformation (ln) of non-normally distributed variables, univariate and multivariate linear regression analyses were performed to determine the association between sleep quality measures and each of these variables, and the results are represented as standardized coefficients (beta). In the multivariate analysis, the model was adjusted for the traditional confounders age, menopause duration, and BMI, and for the non-traditional possible confounder FSH [20,21]. A two-tailed P value < 0.05 was considered to be statistically significant.…”
Section: Methodsmentioning
confidence: 99%
“…After log-transformation (ln) of non-normally distributed variables, univariate and multivariate linear regression analyses were performed to determine the association between sleep quality measures and each of these variables, and the results are represented as standardized coefficients (beta). In the multivariate analysis, the model was adjusted for the traditional confounders age, menopause duration, and BMI, and for the non-traditional possible confounder FSH [20,21]. A two-tailed P value < 0.05 was considered to be statistically significant.…”
Section: Methodsmentioning
confidence: 99%
“…Overexpression of LHR in cultured Hec1A endometrial cancer cells has previously been shown to increase the ability of tumors arising from these cells to invade and metastasize (Pillozzi et al, 2013). In a study on rheumatoid arthritis it was demonstrated that percent increase in LH and FSH levels correlated with changes in a number of proinflammatory molecules and other markers of disease activity (Kåss et al, 2010). Thus, blocking or downregulating LH could prove not only beneficial for Alzheimer's disease progression, but also as a way to slow the progression of a number of agerelated disorders.…”
Section: Novel Therapies and Future Directionsmentioning
confidence: 96%
“…In brief, FSH has been reported to induce TNF in vitro (Iqbal et al, 2006), and high LH and FSH levels have allowed the rationalization, through their association with high TNF and IL-1␤, of the onset or exacerbation of rheumatoid arthritis in women at menopause (Kåss et al, 2010). As we have noted (Clark and Atwood, 2011), the antigonadotropic actions of leuprolide render it an anti-mitotic and anti-inflammatory agent when used to treat endometriosis.…”
Section: Tnf Causes Insulin Resistance: Implications For Admentioning
confidence: 99%